The Nutrient Composition of Fermented Maize Stover with Different Fermentors - Yanuarianto, Oscar; Noersidiq, Azhary; Amin, Muhamad; Dilaga, Syamsul Hidayat; Dahlanuddin, Dahlanuddin; Imran, Tya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
In tropical areas like Indonesia, the presence of forage feed is significantly impacted by seasonal changes, resulting in abundance during the wet season and scarcity during the dry season. Agricultural waste is a solution as an alternative animal feed, one of which is corn stover. Research aimed at determining the nutritional composition of corn stover fermented with different fermentor was conducted at the Nutrition and Animal Feed Laboratory, Faculty of Animal Science, University of Mataram. This research was organized based on a completely randomized design with four treatments and five replications. They were T0: 1 kg corn stover (CS) without treatment, T1: 1 kg CS + 40 g Saccharomyces cerevisiae (SC); T2: 1 kg CS + 40 ml MA-11; T3: 1 kg CS + 20 gr SC + 20 ml MA-11. The variables observed were physical properties such as colour, texture and aroma and nutritional content (Dry matter (DM), Organic matter (OM), Crude Protein (CP), Crude Fibre (CF) and Crude Fat (CFa). The results showed that the addition of SC and MA-11 not give a significant effect (P>0.05) on CFa. However, the addition of them had a significant effect (P<0.05) on the decrease of DM, BO and SK content and the increase of PK content. The highest average BK and OM contents were obtained in T0 (control) at 81.44%, and 82.20%, the highest average CP and CFa contents were obtained in T2 (MA-11) at 9.36%, and 1.90%. The lowest average CF content was obtained in T2 (MA-11) at 26.40%.